Comparative Study: Implementation of Merdeka Curriculum in Senior High Schools in Indonesia - Samuna, Wa; Jabar, Cepi Safruddin Abd (UNIVERSITAS PAKUAN, 2025)
The purpose of the study is to analyze the implementation of the independent curriculum in Sekolag Menegah Atas in Indonesia. This research is a descriptive research with a qualitative approach. The subjects of this study are the principal and vice principal of the curriculum. The location of this research is SMA Negeri 1 Sebuku and SMA Negeri 1 Sembakung. Data collection was carried out through interviews, documentation studies, and observations. Data analysis is carried out through stages: 1) collecting data, 2) summarizing and selecting the main things and looking for themes, 3) presenting data in the form of a brief description, and relationships between categories, 4) drawing conclusions, and 5) building and explaining theories. The results of the study showed SMEs at SMA Negeri 1 Sebuku and SMA Negeri 1 Sembakung have been running through several preparations. The curriculum structure is prepared by considering the availability of teachers. The implementation of P5 at SMA Negeri 1 Sebuku is carried out with a block system while SMA Negeri 1 Sembakung uses a regular system. The implementation of IKM at SMA Negeri 1 Sebuku and SMA Negeri 1 Sembakung received support from the Education and Culture Office, school supervisors and parents/guardians of students. In addition, SMA Negeri 1 Sebuku as a driving school also received support from the Driving Teacher Center. In addition, the IKM Strategy at SMA Negeri 1 Sebuku and SMA Negeri 1 Sembakung began with socialization activities and then continued with the improvement of teacher human resources through Workshop and training activities that presented resource persons in house training, independent learning through PMM, carrying out imitation studies at driving schools that have implemented IKM, sharing with fellow teachers and/or with the principal, as well as participating in the Driving Teacher Program.